1966
DOI: 10.1113/jphysiol.1966.sp008044
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the maximal rate of organic anion secretion by the liver and further evidence on the hepatic site of action of the hormone secretin

Abstract: SUMMARY1. Bromsulphthalein (BSP) was administered throughout the experiments at a constant rate well in excess of its excretory rate, to anaesthetized dogs in which the common bile duct had been cannulated. The maximal excretory rate of BSP into bile (BSP Tm) obtained in this manner was greatly elevated by choleresis arising from the administration of bile salt (usually taurocholate) at constant rate.2. When bile flow rate was increased in stages by raising the taurocholate administration rate, successive incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2

Year Published

1972
1972
1989
1989

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(46 citation statements)
references
References 10 publications
4
40
2
Order By: Relevance
“…The maximum rate at which it is transported into bile may be affected by the excretion of bile salt. It is believed that this is due to the decrease in the biliary concentration of BSP which occurs as bile flow is increased (O'Maille, Richards & Short, 1966). BSP, unlike the bile salts, is a disodium salt, and thus the marked increase in the concentration of sodium in bile, during the excretion of BSP in bile, is not unexpected.…”
Section: Bromsulphthaleinmentioning
confidence: 99%
“…The maximum rate at which it is transported into bile may be affected by the excretion of bile salt. It is believed that this is due to the decrease in the biliary concentration of BSP which occurs as bile flow is increased (O'Maille, Richards & Short, 1966). BSP, unlike the bile salts, is a disodium salt, and thus the marked increase in the concentration of sodium in bile, during the excretion of BSP in bile, is not unexpected.…”
Section: Bromsulphthaleinmentioning
confidence: 99%
“…Physiological studies of bilirubin and other organic anion secretory rates in bile showed a strong correlation with bile acid secretory rates under stimulated conditions but not during fasting (3)(4)(5)(6)(7)(8). This observation led to studies that have concluded that a strong relationship exists between biliary mixed-lipid micelles and bilirubin in addition to a variety of other organic anions, although the precise nature of the putative micellar-organic anion interaction has remained unclear (9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…In the present experiments it was evident that a maximal biliary concentration of BSP was a limiting factor in the biliary excretion and that excretion of BSP above this level was directly proportional to the increase in bile flow. Increased bile flow associated with supramaximal rates of BSP excretion has been reported in the rat (Dhumeaux et al, 1970), the sheep (Gronwall and Cornelius, 1970), and the dog (O'Maillie et al, 1966). It has been suggested that this choleresis is due to an increased excretion of bile acids with a nett increase in bile flow and biliary excretion of BSP.…”
Section: Discussionmentioning
confidence: 88%
“…There are a variety of factors which might influence the hepatic handling of BSP and these include liver blood flow (Shoemaker et al, 1961), body temperature (Harris, Noble and Munday, 1975), bile flow (Boyer, Scheig and Klatskin, 1970), bile salt concentration and competitive excretion with other organic anions (O'Maillie, Richards and Short, 1966). Care was taken to eliminate the effects of other drugs, particularly anaesthetic agents; experiments were performed in a constant temperature environment and the animals were subjected to minimal stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation